Is fresh-frozen plasma clinically effective? An update of a systematic review of randomized controlled trials. - Yang, L; Stanworth, S; Hopewell, S; Doree, C; Murphy, M (2012)
BACKGROUND: The clinical use of frozen plasma (FP) continues to increase, both in prophylactic and in therapeutic settings. In 2004, a systematic review of all published randomized controlled trials (RCTs) revealed a lack of evidence that supported the efficacy of FP use. This is an update that includes all new RCTs published since the original review. STUDY DESIGN AND METHODS: Trials involving transfusion of FP up to July 2011 were identified from searches of MEDLINE, EMBASE, CINAHL, The Cochrane Library, and the UKBTS/SRI Transfusion Evidence Library. Methodologic quality was assessed. The primary outcome measure was the effect of FP on survival. RESULTS: Twenty-one new trials were eligible for inclusion. These covered prophylactic and therapeutic FP use in liver disease, in cardiac surgery, for warfarin anticoagulation reversal, for thrombotic thrombocytopenic purpura treatment, for plasmapheresis, and in other settings, including burns, shock, and head injury. The largest number of recent RCTs were conducted in cardiac surgery; meta-analysis showed no significant difference for FP use for the outcome of 24-hours postoperative blood loss (weighted mean difference, -35.24 mL; 95% confidence interval, -84.16 to 13.68 mL). Overall, there was no significant benefit for FP use across all the clinical conditions. Only two of the 21 trials fulfilled all the criteria for quality assessment. CONCLUSION: Combined with the 2004 review, 80 RCTs have investigated FP with no consistent evidence of significant benefit for prophylactic and therapeutic use across a range of indications evaluated. There has been little improvement in the overall methodologic quality of RCTs conducted in the past few years.